Rousseau between nature and culture : philosophy, literature, and politics - Deneys-Tunney, Anne; Zarka, Yves Charles (Culture & conflict ;, 2016)
Rousseau has been seen as the inventor of the concept of nature; in this collective volume philosophers and literary specialists from France and the United States examine how Rousseau's philosophy can be reinterpreted from the point of view of a constant dialectical debate between nature and culture. In this, Rousseau is our true contemporary.--